Effects of di(2-ethylhexyl) phthalate on glucose homeostasis in rats due to impaired autophagy flux of islet β cells mediated by oxidative stress - Hongyang ZHOU; Yuting HU; Xue CHEN; Yunqiang ZHOU; Liping LI; Ling LI; Herong LIU (环境与职业医学)
BackgroundDi(2-ethylhexyl) phthalate (DEHP) is the most prevalent environmental endocrine disruptor among phthalate acid esters (PAEs) worldwide. Previous studies have indicated that exposure to DEHP may disrupt glucose metabolism.ObjectiveTo investigate the impact of DEHP on glucose homeostasis in rats, focusing on oxidative stress-induced impairment of autophagy in islet β cells.MethodsForty male SD rats were randomly assigned to four groups, receiving DEHP doses of 0, 187, 375, and 750 mg·kg−1 for 12 weeks. Oral glucose tolerance (OGTT) and insulin tolerance tests (ITT) were conducted 24 h after the final exposure. Pancreatic microstructural alterations were assessed using hematoxylin and eosin (HE) staining and transmission electron microscopy (TEM). Commercial ELISA kits were employed to quantify the levels of insulin, adenosine triphosphate (ATP), and adenosine monophosphate (AMP) in rat serum, as well as the protein expression level of activated caspase-3 in pancreatic tissue. Additionally, commercial microplate kits were utilized to measure the concentration of reduced glutathione (GSH) in serum, the activity of superoxide dismutase (SOD) using water-soluble tetrazolium salt-1, the content of malondialdehyde (MDA) by thiobarbituric acid method, and the level of reactive oxygen species (ROS) in pancreatic tissue by chemical fluorescence method. Reverse transcription polymerase chain reaction (RT-PCR) was used to measure sequestosome1 (SQSTM1/p62), Beclin1, microtubule-associated protein 1 light chain 3 (LC3), and cysteinyl aspartate specific proteinase-8 (Caspase-8) mRNA levels. Western blot analysis was applied to detect the protein relative expression levels of p62, Beclin-1, LC3-I, LC3 II, AMPK, p-AMPK, mTOR, p-mTOR, ULK1, and Caspase-8.ResultsCompared to the 0 mg·kg−1 DEHP group, the 750 mg·kg−1 DEHP group exhibited a significant increase in fasting blood glucose levels at 2, 4, 6, and 12 weeks (P<0.05). The OGTT showed that, following high-glucose gavage, the 187 mg·kg−1 DEHP group had elevated blood glucose at 30 min (P<0.05), the 375 mg·kg−1 DEHP group showed increased glucose levels at 15, 30, and 180 min (P<0.05), and the 750 mg·kg−1 DEHP group exhibited elevated levels at 15, 30, 60, and 180 min (P<0.05). The 375 and 750 mg·kg−1 DEHP groups demonstrated significantly increased OGTT area under the curve (AUC) values (P<0.05). In contrast, ITT results indicated no significant differences in blood glucose levels or AUC among the DEHP exposure groups at all time points (P>0.05). Compared to the 0 mg·kg−1 DEHP group, the 750 mg·kg−1 DEHP group exhibited significantly higher HOMA-IR levels and markedly lower HOMA-ISI values (P<0.05). HE and TEM showed that in each DEHP exposure group, the number of islet cells decreased, the islet area reduced, and chromatin condensation occurred. The endocrine granules in the cytoplasm of islet β cells decreased, and there were varying degrees of widening of the nuclear membrane gap, flattening and expansion of the Golgi complex, and expansion of the endoplasmic reticulum. Ribosome separation was observed, and autophagosomes were visible. In the 375 and 750 mg·kg−1 DEHP groups, the mitochondria were deformed to varying degrees, and some cristae structures disappeared, presenting vacuolization. Moreover, the chromatin condensation in the nuclei was more severe in the 750 mg·kg−1 DEHP group. The serum SOD activity was significantly elevated in the 750 mg·kg−1 DEHP group (P<0.05). Both the 375 mg·kg−1 and 750 mg·kg−1 DEHP groups exhibited a significant increase in the relative ROS content in pancreatic tissue (P<0.05). In DEHP-treated groups, the MDA content increased (P<0.05), while the GSH content decreased (P<0.05). Additionally, in the 750 mg·kg−1 DEHP group, the AMP/ATP ratio in serum was significantly raised (P<0.05), and the expression of cleaved Caspase-3 protein in pancreatic tissue was also significantly increased (P<0.05). The relative mRNA levels of p62, Beclin-1, LC3, and Caspase-8 in the pancreatic tissue of rats exposed to DEHP were significantly elevated (P<0.05). The relative expression levels of p-AMPK/AMPK, p-ULK1/ULK1, and Beclin-1 proteins in the DEHP-treated groups were significantly increased (P<0.05). In the 375 mg·kg−1 and 750 mg·kg−1 DEHP treatment groups, the relative expression levels of p62, LC3 II/LC1, and Caspase-8 proteins were significantly increased (P<0.05), while the relative expression level of p-mTOR/mTOR was significantly decreased (P<0.05).ConclusionDEHP can disrupt glucose homeostasis by inducing oxidative stress, which subsequently activates autophagy via the ROS/AMPK/ULK1 pathway, impairing autophagic flux and promoting apoptosis of islet β cells, ultimately decreasing their function and number.